Foundation of Ex Manubiis Temple in the Circus Flaminius - Jarych, Adam Jakub (Acta Archaeologica Lodziensia, 2020)
The use of booty on construction activity in ancient Rome, was practiced in the times of the Kings, when Tarquinius financed the construction of the Temple of Jupiter in such a way. In this article, I would like to gather together the ex manubiis foundations, which were erected during the whole period of the Republic within the Circus Flaminius. According to the surviving literary and archaeological sources, we can detect this method being used to finance the building of temples in the case of nine buildings. The Circus Flaminius was a very important area for victorious generals on account of their being able to present the effects of their military campaigns. Moreover, at this point run triumphal road, which was flanked on each side with ex manubiis temples which emerged almost every year.